Solusi Inovatif dalam Pengelolaan Sampah Organik di Lingkungan Sekolah Menggunakan Metode Takakura - Muhammad Rifki Setiawan; Nuril Hidayat; Andik Prasetyo; Muhammad Zaien Maulana; Yuarfi Kukuh Pratama; Moch. Faisal Basri; Muhammad Yusniar Fahmi; Rachmadhani Afif Saputra; Ahmad Fauzi; Eka Widya Maharani; Ardhana Rahmayanti; Laily Noer Hamidah; Iqbal Faizin; Elmi Sumiyarsono (Journal of Science and Social Development, 2023)
Household waste is a type of waste that contributes to environmental pollution. Waste can cause a nuisance if it is not handled seriously. Sixty-eight percent of the waste in the school environment consists of organic waste, which is a type of waste that can be decomposed by bacteria. Composting is one of the right methods for dealing with wasterelated problems. Takakura is a composting method that can be implemented by the general public because the method is simple and easy to apply. The method used is an interactive counseling method and demonstration via video in introducing Takakura compost making. The results obtained from this activity were that participants were enthusiastic and happy to take part in this activity because they gained additional knowledge in managing household organic waste, which can produce compost as a final product, and can be sold to provide additional family income.